Simple interference based colorization of Si based solar cells and panels with ITO/SiNx:H double layer antireflective coatings. (1st September 2020) - Rudzikas, Matas; Šetkus, Arūnas; Stange, Marit; Ulbikas, Juras; Ulyashin, Alexander
Highlights: Simple, cost effective and efficiency beneficial method for coloring of solar cells. ITO properties are crucial for the efficiency, but not for the color of a DLARC cell. Wide palette of homogenous colors was produced. Solar module with 185 nm ITO coated cells resulted in 1.5% less power than without. Abstract: The integration of solar modules into buildings offers a highly attractive area for enlarging the market of commercial solar cells. Therefore, cost-effective industrial approaches to fabricate solar cells and relevant modules with different colors are required. In this work a simple method for applying individual color to Si based solar cells was adapted to the industrially fabricated commercial cells with standard SiNx :H antireflection coating (ARC) and also explicitly described by a fundamental model. This method of coloring is based on the optical interference effect in the layered structure. The structure includes a thin indium tin oxide (ITO) layer deposited on the top of the ARC. An intentional change of the ITO thickness from 0 to 240 nm resulted in a change of the color through the visible spectrum. The color was added to multi- as well as mono-Si based industrially fabricated textured solar cells with conventional blue color ARC. Reasonable agreement between the theoretical and experimental results has been obtained from the model calculations. For the proof of concept, a mini-solar-module with six green cells was fabricated that were coated by an ITO (185 nm)/SiNx :H double layer ARC stack. It is shown that the efficiency of such module is only about 1.5% lower than that of the mini-module manufactured using reference industrial cells with SiNx :H ARC only. It is concluded that the proposed approach can be considered as a cost-effective method to fabricate coloured Si based cells and relevant modules using only one simple technological step.